Education and Examination of Infants and Toddlers in RW06 Babakan Asih Urban Village Bandung City - Sihombing, Kristin; Triana, Hani; Fauziah, Liliek; Ardayani, Tri; Sudjana, Treesia; Sarce, Sari (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
The purpose of this activity is to plan community service activities to solve problems obtained based on situation analysis, and determination of problem priorities by providing health education to the community so that they always maintain health. The method used consists of preparation, implementation, and closing. Preparations are carried out with various activities, including field surveys, problem identification, approaches to the community, situation analysis, and proposal preparation carried out in August 2024. The implementation will be held on November 12, 2024, from 08.00 to 10.00 WIB at the RW 06 office of Babakan Asih Village, Bandung City. The implementation of community service activities regarding Health Education Education regarding nutrition in infants and toddlers as well as weight and height weighing, can be carried out well and smoothly and conducively. The results of the activity showed that public knowledge about the meaning of nutrition in infants and toddlers increased and no infants and toddlers experienced malnutrition. This community service activity is expected to bring real benefits to the people of Babakan Asih Village, Bandung City and become an inspiration for similar efforts in various regions.